The Independence of Civil Servant Investigators in Indonesian Immigration: A Fiqh Siyasah Perspective - Anis Mashdurohatun; Deny Arly Asmara; Erwin Zainul Hakim; Agung Hadi Wijanarko; Zekry Abd Elrazik Mohamed Ali (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
In handling immigration-related criminal offenses, overlapping authority between Immigration Civil Servant Investigators (PPNS) and police investigators remains a regulatory and practical issue. The limited scope of authority granted to PPNS highlights the need to reexamine existing legal provisions through the lens of fiqh siyasah (Islamic political jurisprudence). This study aims to analyze how fiqh siyasah, particularly the principles of ta‘addud al-wilāyah (plurality of authority) and tafwidh al-sulthah (delegation of power), can be used to reconstruct the authority of Immigration PPNS in carrying out independent investigative functions. Employing a normative legal research approach, the study finds that from the perspective of fiqh siyasah, it is normatively justifiable for Immigration Civil Servant Investigators to operate autonomously as part of the delegated authority of the state (ulil amri). The study recommends amending Article 7, paragraph (2) of the Indonesian Criminal Procedure Code by replacing the phrase “under coordination and supervision” with “may coordinate,” as an effort to strengthen the institutional position of PPNS within Indonesia’s law enforcement system. The academic contribution of this study lies in offering an Islamic jurisprudential framework to critically assess and reform the institutional structure of legal authority in Indonesia, thereby integrating normative Islamic thought into the discourse of contemporary legal policy reform